Methadone for cancer pain - Nicholson, Alexander B (Cochrane Database Syst Rev, 2017)
BACKGROUND: This is an updated review originally published in 2004 and first updated in 2007. This version includes substantial changes to bring it in line with current methodological requirements. Methadone is a synthetic opioid that presents some challenges in dose titration and is recognised to cause potentially fatal arrhythmias in some patients. It does have a place in therapy for people who cannot tolerate other opioids but should be initiated only by experienced practitioners. This review is one of a suite of reviews on opioids for cancer pain. OBJECTIVES: To determine the effectiveness and tolerability of methadone as an analgesic in adults and children with cancer pain. SEARCH METHODS: For this update we searched CENTRAL, MEDLINE, Embase, CINAHL, and clinicaltrials.gov, to May 2016, without language restriction. We also checked reference lists in relevant articles. SELECTION CRITERIA: We sought randomised controlled trials comparing methadone (any formulation and by any route) with active or placebo comparators in people with cancer pain. DATA COLLECTION AND ANALYSIS: All authors agreed on studies for inclusion. We retrieved full texts whenever there was any uncertainty about eligibility. One review author extracted data, which were checked by another review author. There were insufficient comparable data for meta‐analysis. We extracted information on the effect of methadone on pain intensity or pain relief, the number or proportion of participants with 'no worse than mild pain'. We looked for data on withdrawal and adverse events. We looked specifically for information about adverse events relating to appetite, thirst, and somnolence. We assessed the evidence using GRADE and created a 'Summary of findings' table. MAIN RESULTS: We revisited decisions made in the earlier version of this review and excluded five studies that were previously included. We identified one new study for this update. This review includes six studies with 388 participants. We did not identify any studies in children. The included studies differed so much in their methods and comparisons that no synthesis of results was feasible. Only one study (103 participants) specifically reported the number of participants with a given level of pain relief, in this case a reduction of at least 20% ‐ similar in both the methadone and morphine groups. Using an outcome of 'no worse than mild pain', methadone was similar to morphine in effectiveness, and most participants who could tolerate methadone achieved 'no worse than mild pain'. Adverse event withdrawals with methadone were uncommon (12/202) and similar in other groups. Deaths were uncommon except in one study where the majority of participants died, irrespective of treatment group. For specific adverse events, somnolence was more common with methadone than with morphine, while dry mouth was more common with morphine than with methadone. None of the studies reported effects on appetite. We judged the quality of evidence to be low, downgraded due to risk of bias and sparse data. For specific adverse events, we considered the quality of evidence to be very low, downgraded due to risk of bias, sparse data, and indirectness, as surrogates for appetite, thirst and somnolence were used. There were no data on the use of methadone in children. AUTHORS' CONCLUSIONS: Based on low‐quality evidence, methadone is a drug that has similar analgesic benefits to morphine and has a role in the management of cancer pain in adults. Other opioids such as morphine and fentanyl are easier to manage but may be more expensive than methadone in many economies.